2017
DOI: 10.1037/xge0000254
|View full text |Cite
|
Sign up to set email alerts
|

Time on your hands: Perceived duration of sensory events is biased toward concurrent actions.

Abstract: Perceptual systems must rapidly generate accurate representations of the world from sensory inputs that are corrupted by internal and external noise. We can typically obtain more veridical representations by integrating information from multiple channels, but this integration can lead to biases when inputs are, in fact, not from the same source. While a considerable amount is known about how different sources of information are combined to influence what we perceive, it is not known whether temporal features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
5
31
0
Order By: Relevance
“…For the middle and most ambiguous interval in the stimulus set, choice location could be determined well before the stimulus offset occurred. Notably, longer movements on these trials more often led subjects to classify the stimulus as "long", concordant with previous findings (Yokosaka et al, 2015;Yon et al, 2017). However, even when taking this into account, the divergence between target proximities is striking, with a separation by 1500ms into the trial that is predictive of choice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For the middle and most ambiguous interval in the stimulus set, choice location could be determined well before the stimulus offset occurred. Notably, longer movements on these trials more often led subjects to classify the stimulus as "long", concordant with previous findings (Yokosaka et al, 2015;Yon et al, 2017). However, even when taking this into account, the divergence between target proximities is striking, with a separation by 1500ms into the trial that is predictive of choice.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has begun to demonstrate a strong influence of the motor system on temporal processing. A variety of studies now demonstrate how movement parameters can influence the perceived duration of a stimulus, with longer movements typically associated with longer perceived durations (Yon et al, 2017;Yokosaka et al, 2015;Hagura et al, 2012). We find some support for this in our paradigm, with freemovement subjects classifying auditory tones as "long" more often when their arm movements during the interval were also longer.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These are known as examples in which actions distort our perception of time. Although an increasing number of studies have accumulated behavioral evidence for this actioninduced time distortion (Hagura, Kanai, Orgs, & Haggard, 2012;Iwasaki et al, 2017;Merchant & Yarrow, 2016;Morrone, Ross, & Burr, 2005;Press, Berlot, Bird, Ivry, & Cook, 2014;Tomassini & Morrone, 2016;Yokosaka, Kuroki, Nishida, & Watanabe, 2015;Yon, Edey, Ivry, & Press, 2017), no study has revealed specific neural mechanisms underlying it.…”
Section: Introductionmentioning
confidence: 99%